National Mobilization and Relevance for Defense Education Strategy - Hidayatullah, Syarif; Toni, Toni; Widjayanto, Joni; Purwanto, Ignatius Eko Djoko; Saputro, Guntur Eko (Journal of Social Work and Science Education, 2025)
This study aims to examine the relevance of the concept of total war and national resource mobilization during World War II in the development of modern defense education in Indonesia. The research approach used is descriptive qualitative with historical-contextual analysis methods. Data were obtained through literature studies of primary and secondary sources, including historical documents, academic books, international journals, and lecture materials from defense institutions. The results of the study indicate that the principles of total war, such as total mobilization, industrial conversion, and the formation of collective consciousness, can be used as a strategic learning framework in the defense education system. The novelty of this study lies in the integration of historical analysis of war with a contextual pedagogical approach that is adaptive to contemporary challenges. The main contribution of this article is to offer a conceptual model of history based defense learning that strengthens national deterrence through value education, strategic reflection, and strengthening leadership character. These findings are expected to enrich academic discourse and defense curriculum practices in developing countries.